Making copper, silver and gold fullerene cages breathe. (1st June 2022) - Zhao, W; Jones, R M; D'Agosta, R; Baletto, F
Abstract: We show that optical properties change when the fullerene structures of Au32, Cu32 and Ag32 inflate and deflate. We first observe significant differences in the extinction spectra employing a classical approach based on the Green's dyadic method. By means of real-time time-dependent density functional theory. We continue to calculate the optical spectrum (OP) via a δ -kick simulation, comparing results with the ground-state energetic property the HOMO–LUMO (HL) gap. Red-shift of the OP is expected as the fullerenes inflate, with only ±10% change in the size. As the fullerene breathes, a 0.8 eV shift in the first peak position could be observed in the gold nanoparticle. Ag has a smoother behaviour than both Au and Cu. We have also found changes in the optical spectra can not be directly interpreted as a result of changes in the HL gap.